PENGEMBANGAN AGRIBISNIS BERBASIS ARAK DI SUBAK ABIAN TELUN WAYAH DESA TRI EKA BUANAN, KECAMATAN SIDEMEN. KABUPATEN KARANGASEM - I Wayan Rideng; Gst Bgs. Udayana; I Made Minggu Widyantara (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The life of the people in Bali, which breathes customs and culture, provides support for tourism development. The island of Bali always gets the best award as one of the world's tourist destinations. The Covid-19 pandemic, which lasted almost 2 years, has weakened the tourism sector in Bali. Community life, which is religious with routines, is the main attraction. As one part or element in the series of ceremonies, is the availability of Arak facilities. Arak is served in a ritual process associated with a series of Hindu religious ceremonies called Yadnya. In the era of the Covid-19 pandemic, the existence of arak, which has been known as a traditional drink, has received attention because it is believed by researchers or Usada that it can prevent exposure to the Virus-19. Observing this, the Provincial Government has issued and Regional Regulation Number 1 of 2020 concerning Governance for Fermented Drinks and/or Distilled Balinese Drinks. The enactment of this regulation shows that the Bali Provincial Government has been present in order to provide legal protection and legal certainty for the production of arak and its circulation. One of the areas for the production of Arak is the people of Tri Eka Buana Village, Sidemen District, Karangasem Regency.